Methodological analysis of stature estimation from tibia osteometric data - Océane Monteiro; Bérengère Saliba-Serre; Philippe Lefèvre; Émeline Verna; Loïc Lalys (Forensic Science International: Reports, 2022)
Objectives: Stature is one of the characteristic elements of the biological profile, allowing the identification of human bone remains in a forensic context. Stature has a strong relationship of proportionality with the long bones of the lower limb. This study focuses on the biometric exploitation of the whole-bone tibia to estimate stature. The objective is to evaluate the performance of different stature estimation methods using various measurements. In addition, the use of age correction factors was studied in order to observe their influences. Materials and Methods: The study was based on a sample of 91 tibias (43 males and 48 females) from the Belgian population for which 20 standard measurements were taken. A total of 28 regression equations from eight methods were used with or without the inclusion of two correction factors. The performance of the methods was evaluated by exploiting the estimation errors and the number of individuals included in the area of acceptability defined for the study. Results: The tibia measurements were reproducible. The most effective for stature estimation were bone lengths. The whole-bone methods developed in the 21st century was the most efficient, and the application of correction factors allowed for the improvement of the equations. Discussion and conclusion: The best performing method is Nikita et al. 2017, and the correction age best emphasizing stature estimation was 30 years. Equations for females provided the majority of the best results, followed by those for undetermined sex.